ANALYSIS OF DEVELOPMENT OF DERADICALIZATION OF TERRORIST PRISONERS IN THE CORRECTIONAL INSTITUTIONS IN INDONESIA - Asdira, Yusril Arinaldy (Bisma The Journal of Counseling, 2020)
Terrorism is a problem that requires special handling, one of which is by fostering deradicalization. In Indonesia according to data obtained that de-radicalization is considered unsuccessful because there are still many terrorists who dare to commit acts of terrorism even though many other terrorists have been arrested. One of the indications is like the North Sumatra Poltabes office bombing incident in November 2019 where the Police arrested 74 suspected terrorists involved in the suicide bombing. This study aims to determine the various activities carried out for deradicalisation guidance and to see the achievements of deradicalization coaching .The research method used is descriptive qualitative research method with literature study approach. The results show that various activities have been carried out by the government one of them is create BNPT a special institution to manage and implement deradicalization of terorrism prisoners through soft approach to deradicalize terrorist prisoners by reshaping their thinking about the struggle against religion. The conclusion is that the development of deradicalization of terrorist prisoners in Indonesia has been carried out by various parties, but based on the results of this study and previous research is still not optimal so it needs to be reviewed about the type or method of fostering deradicalization that is appropriate.